EDUCATIONAL MEDIA TO INCREASE MOTHER’S KNOWLEDGE OF EXCLUSIVE BREASTFEEDING: A LITERATURE REVIEW - Gina Nurul Azmi; Lilis Mamuroh; Sri Hendrawati (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2022)
Currently, the coverage of exclusive breastfeeding in Indonesia has not reached the target. One of the reasons is the lack of information (transfer of knowledge) by health workers about exclusive breastfeeding for pregnant women, breastfeeding mothers, and their families. One of the reasons is the lack of use of the media by officers when providing counseling. Each officer should be able to choose the right method so that all the information provided can be controlled by the mother and her family. This research will examine the success of counseling through the right media to help increase the knowledge of mothers about exclusive breastfeeding. This study uses a literature study method with a narrative review approach. The databases used are Google Scholar and PubMed with the keywords media education, health education, counseling, knowledge, pregnant mother, breastfeeding mother, exclusive breastfeeding, six months breastfeeding. The inclusion criteria consisted of original research, full text articles, 2015-2020 article published years, samples of breastfeeding mothers and pregnant women, educational articles or counseling or health education about exclusive breastfeeding, and 11 articles that met the inclusion. Literature studies show that the effective use of printed media can increase knowledge about exclusive breastfeeding, namely leaflets, posters, flipcharts and booklets. While electronic media that can be used include audiovisual media, power point shows, animation, films and websites. Thus, the most effective media used is a combination of print media and electronic media. The distribution of printed media in the form of booklets after counseling using electronic media (audiovisual) is intended so that respondents can remember things that have been discussed during the counseling. For health workers, it is advisable to first consider the media that will be used in providing education or counseling or health promotion regarding exclusive breastfeeding.